2023
DOI: 10.1002/mp.16448
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Experimental dosimetric characterization of proton pencil beam distortion in a perpendicular magnetic field of an in‐beam MR scanner

Abstract: BackgroundAs it promises more precise and conformal radiation treatments, magnetic resonance imaging‐integrated proton therapy (MRiPT) is seen as a next step in image guidance for proton therapy. The Lorentz force, which affects the course of the proton pencil beams, presents a problem for beam delivery in the presence of a magnetic field.PurposeTo investigate the influence of the 0.32‐T perpendicular magnetic field of an MR scanner on the delivery of proton pencil beams inside an MRiPT prototype system.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition to the dependence of c ⃗ B on the lateral position, as discussed by Oborn et al 14 and Gebauer et al 15 due to lateral displacement and field deformation towards the field edges, it is important to note that c ⃗ B also exhibits deviations from unity in the Bragg peak region. These deviations remained small in the central regions of the field, but the Bragg peak region showed noticeable effects on the absorbed dose-to-water influenced by the MF.…”
Section: Impact Of Perpendicular Magnetic Fields On Proton Dosimetrymentioning
confidence: 86%
See 2 more Smart Citations
“…In addition to the dependence of c ⃗ B on the lateral position, as discussed by Oborn et al 14 and Gebauer et al 15 due to lateral displacement and field deformation towards the field edges, it is important to note that c ⃗ B also exhibits deviations from unity in the Bragg peak region. These deviations remained small in the central regions of the field, but the Bragg peak region showed noticeable effects on the absorbed dose-to-water influenced by the MF.…”
Section: Impact Of Perpendicular Magnetic Fields On Proton Dosimetrymentioning
confidence: 86%
“…Grevillot et al 32 used the same beamline and observed only minor fluctuations in the proton field homogeneity for a shifted field. In addition, Gebauer et al 15 reported minimal relative shifts (<0.5 mm) of proton pencil beams within the central 5 × 5 cm 2 region of a proton field measured in a 0.32 T MRI machine. This suggests that potential uncertainties arising from a proton field shift are unlikely to have a substantial effect on the measurement results in our study.…”
Section: Measurement and MC Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation